Strutture operative e logiche costituzionali del regime di Cesare - Scevola, Roberto (Tesserae iuris, 2023)
Aiming to widen the field of research opened by the analysis of the constitutional framework of Caesarian dictatorships, to which he has dedicated an earlier essay, the author discusses operative structures and constitutional approaches of Caesar’s government as progressively established in the years 49-44 BCE. Preliminary to some remarks on the debate about the supposed lack of an overall project responding to a clear conception of a constitutional nature, the several means through which Caesar transformed in a hierarchical and personalistic way the republican order are fully analyzed: in essence, they show the tendency to enact a civile imperium, that is, to the reproposal - with the necessary accomodations - of the ‘chain of command’ that had marked his military achievements, responding to a specific conception of rem publicam gerere rather than to temporary demands.